Empresários Portugueses na Diáspora - Tendências Recentes - Catarina da Costa Tavares Silva (2019)
The present study aims to understand which are the main trends currently thriving in the world, relatively to the new Portuguese entrepreneurs who develop a business outside Portugal and their main sectors of investment. The research is focused in the comprehension of the Portuguese entrepreneurs' characteristics, and their contribution in the diaspora. This research also analyses the motivations that lead these entrepreneurs to decide to undertake in the foreign country, becoming hence relevant investigate the influence that Portugal - the origin country - has on these entrepreneurs. For this purpose, we developed the concepts of entrepreneurship and emigration, with a special emphasis on the Portuguese matters, being the literature review widely focused on that point of view. The methodology adopted was quantitative, with a survey being sent to Portuguese entrepreneurs in the diaspora, through the Associations of Portuguese Emigrants, the International Chambers of Commerce, the Associations of Portuguese Entrepreneurs, the Portuguese Consulates and some personal contacts, counting with the support of Portuguese Diaspora Council, Council of Portuguese Communities and the Office for Diaspora Investors Support (GAID), in order to obtain valuable information regarding this topic.